Multi-Modal 2020: Multi-Modal Argumentation 30 Years Later - Gilbert, Michael A. (Informal Logic)

(untitled) (Informal Logic, 2022)
My essay, “Multi-modal argumentation” was published in the journal, Philosophy of the Social Sciences, in 1994. This information appeared again in my book, Coalescent argumentation in 1997. In the ensuing twenty years, there have been many changes in argumentation theory, and I would like to take this opportunity to examine my now middle-aged theory in light of the developments in our discipline. I will begin by relating how a once keen intended lawyer and then formal logician ended up in argumentation theory. (If you do not care to read this bit of autobiography, skip to Section 2).